Troponin‐I levels as a potential prognostic biomarker of sacubitril/valsartan treatment response in heart failure with reduced ejection fraction: Who will benefit most?. Issue 12 (24th November 2018) - Nakou, Eleni S.; Marketou, Maria E.; Chlouverakis, Gregory I.; Patrianakos, Alexandros P.; Vardas, Panos E.; Parthenakis, Fragiskos I.
Abstract : Background: Despite robust data on the benefits of sacubitril/valsartan (LCZ696) in patients with chronic heart failure with reduced ejection fraction (HFrEF), there is no evidence yet on prespecified predictive markers of its efficacy. Hypothesis The objective of this study was to identify potential prognostic factors of LCZ696 treatment response. Methods: We included 48 symptomatic patients with chronic HFrEF (left ventricular ejection fraction ≤35%) and New York Heart Association (NYHA) class II/III: Group A (N = 23) received LCZ696 (105 ± 30 mg twice daily), whereas it was not prescribed in group B (N = 25) according to physician's judgment. Analysis of biochemical parameters, cardiopulmonary exercise testing, and echocardiographic evaluation was performed at baseline and 6 months later. Results: The baseline serum troponin‐I levels (TnI) and peak oxygen uptake (VO2 max) were positively associated with the increase in VO2 max (ΔVO2 max = +14.11%, P < 0.05 vs group B) after sacubitril/valsartan treatment ( r = 0.68, P = 0.001 and r = 0.57, P = 0.004, respectively). Positive correlations were reported between ΔVO2 max and the improvements in the ratio of early diastolic filling to myocardial tissue velocity (ΔE/E′) and the tricuspid annular peak systolic velocity (ΔSa) in group A ( r = 0.58, P = 0.004 and r = 0.60, P = 0.002, respectively). In multiple regression analysis, ΔVO2 max was correlated significantly with TnI (beta = 0.35, P = 0.048), ΔE/E′ (beta = 0.36, P = 0.031) and ΔSa (beta = 0.37, P = 0.035). Conclusions: TnI levels may be an independent predictive marker of sacubitril/valsartan efficacy in HFrEF.